KORELASI KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR KOGNITIF PADA PEMBELAJARAN GEOGRAFI DI SEKOLAH MENENGAH ATAS - Nurzanah, Nurzanah; Tamubolon, Budiman; Harjanti, Diah Trismi (Universitas Tanjungpura, 2023)
The main objective of this research is to examine the connection between students' autonomy in geography education and their cognitive learning achievements in class XI IPS at SMA Negeri 7 Pontianak. The research employed a descriptive method, specifically a correlational study, using correlation research techniques. The study encompassed the entire population of 100 students. Data were collected through indirect communication techniques and documentary study methods. Questionnaires and students' daily test scores served as the data collection instruments. The findings indicated that the level of students' autonomy in geography education for class XI Social Sciences at SMA Negeri 7 Pontianak was 66.78%, categorizing it as